Testing the Monthly Calendar Anomaly of Stock Returns in Pakistan: A Stochastic Dominance Approach (The Pakistan Development Review, 2019)
In this paper, we first examine the presence of monthly calendar anomaly in Pakistan Stock Exchange (PSX) using aggregate and firm-level monthly stock returns. Secondly, we classify the sample firms into low-beta, medium-beta, and high-beta firms to examine the monthly anomaly of stock returns for firms having different level of systematic risk. By considering the stochastic dominance approach (SDA), we employ the simulation based method of Barrett and Donald (2003) to identify the dominant month over the period from January 2000 to December 2017. We find significant evidence of the existence of the January effect in both firm and market stock returns. We also find that the January effect exists more prominently in both low-risk and high-risk firms categorised based on their systematic risk. On the other end of the continuum, for moderately risky firms, there is strong evidence of the presence of the December effect. One of possible explanations of the January effect is the yearend bonus received in the month of January. Such bonuses are generally used to purchase stocks, causing the bullish trend of stock prices in January. However, the evidence of the January anomaly in both low-beta and high-beta portfolios returns is puzzling, suggesting that investors may invest in both low- and high-risk stocks when enthusiastically investing in stock market. The findings of the paper suggest that investors may get abnormal returns by forecasting stock return patterns and designing their investment strategies by taking into account the January and December effects and the level of systematic risk associated with the firms. JEL Classification: G02, G12, G14 Keywords: Behavioural Finance, Stochastic Dominance Approach, Monthly Anomaly, January Effect, December Effect, TOY Anomaly, Abnormal Returns, KS Type Test, PSX